1984
DOI: 10.3109/01485018409161142
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Seminal Plasma Prolactin with Spermatozoal Characteristics and Fertilizing Capacity in Vitro

Abstract: Seminal plasma prolactin (PRL) levels were determined in 224 semen samples collected from fertile and suspected infertile men, and their relationships with spermatozoal characteristics and fertilizing capacity in vitro were evaluated. PRL concentrations were similar in normospermic and oligospermic samples, but were significantly lower in azoospermic samples. PRL concentrations were significantly higher in samples with high spermatozoal motility than in those with low spermatozoal motility. There were no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Physiological concentrations of PRL stimulated metabolism in human spermatozoa in vitro [15] and exhibited putative effects on motility [16,17]. Prolactin has been reported to exert a prosurvival effect on sperm cells [18] as pharmacologic PRL concentrations of 500 ng/mL or greater significantly maintained sperm motility for 19 hours posttreatment as assessed by computer assisted semen analysis.…”
Section: Introductionmentioning
confidence: 98%
“…Physiological concentrations of PRL stimulated metabolism in human spermatozoa in vitro [15] and exhibited putative effects on motility [16,17]. Prolactin has been reported to exert a prosurvival effect on sperm cells [18] as pharmacologic PRL concentrations of 500 ng/mL or greater significantly maintained sperm motility for 19 hours posttreatment as assessed by computer assisted semen analysis.…”
Section: Introductionmentioning
confidence: 98%
“…Our findings also indicated that there was no correlation between seminal PRL levels and sperm morphology. Similarly, Chan et al [ 11 ]. found that seminal levels of PRL did not differ between normozoospermic and teratozoospermic men.…”
Section: Discussionmentioning
confidence: 90%
“…Tang and Chan [ 30 ] reported that the seminal levels of PRL in azoospermic patients were significantly lower than in normozoospermic men. Moreover, Chan et al [ 11 ] found that seminal levels of PRL did not meaningfully differ between normozoospermic and oligozoospermic men, but were significantly lower in azoospermic men. They also reported that seminal PRL concentrations were higher in subjects with higher sperm motility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations